Development of Student Musician’s Methodological Competence in Practice-Oriented University Environment - DYGANOVA, Elena Aleksandrovna; YAVGILDINA, Zilia Muhtarovna (Utopía y Praxis Latinoamericana, 2020)
. ABSTRACT The article reflects the experience of solving the issue of developing and implementing efficient pedagogical means into higher education practice. The goal of the study is the academic justification of the process of methodological competence formation in student musicians within a practice-oriented university environment. The study has shown that certain pedagogical conditions are an efficient means of developing the future music teacher’s methodological competence in the practice-oriented university environment according to federal state requirements for such a specialist’s level of education. RESUMEN El artículo refleja la experiencia de resolver el problema de desarrollar e implementar medios pedagógicos eficientes en la práctica de la educación superior. El objetivo del estudio es la justificación académica del proceso de formación de competencia metodológica en músicos estudiantes dentro de un ambiente universitario orientado a la práctica. El estudio ha demostrado que ciertas condiciones pedagógicas son un medio eficiente para desarrollar la competencia metodológica del futuro profesor de música en el entorno universitario orientado a la práctica de acuerdo con los requisitos del estado federal para el nivel de educación de dicho especialista.